The importance and development of carcass classification and grading in beef cattle: an update - Engin Sakarya; Mustafa Bahadır Çevrimli; Mehmet Saltuk Arıkan (Eurasian Journal of Veterinary Sciences)
This study was conducted to evaluate the current situation in Turkey by providing information about the systems used in carcass classification and grading in beef cattle. Industrial goods and services must have a standard in their economy. Obtaining quality products is provided by production within the framework of determining standards. The carcasses obtained from beef cattle are standardized and graded to ensure their recognition in the market. Standardization and grading; ıt simplifies, facilitates and makes it less costly to move goods across the market channel. In livestock quality standardization, current production is divided into standard shares as much as possible; therefore, animal products are produced in a wide range of quality. The trend in the marketing of high-quality beef animals and carcasses is geared towards grading and yield. Carcass classification is used to accurately define the suitability and values of cattle and sheep carcasses according to their intended use. The main criteria used in the classification of cattle carcasses are weight, conformation and fatness. In the USA and European Union countries, the classification of beef carcasses plays an essential role in international meat trade marketing.